Repeated 177Lu-labeled PSMA-617 radioligand therapy using treatment activities of up to 9.3 GBq - Rathke, Hendrik; Giesel, Frederik L.; Flechsig, Paul; Mier, Walter; Hohenfellner, Markus; Haberkorn, Uwe; Kratochwil, Clemens (Journal of nuclear medicine, 2018)
Current treatment protocols for 177Lu-labeled PSMA-617 therapies were cautiously derived from dosimetry data, but their practical appropriateness has not yet been proven clinically. We retrospectively report our clinical observations using 4 different treatment activities. Methods: Forty patients with advanced prostate cancer and positive uptake in prostate-specific membrane antigen (PSMA) imaging were treated with 4 GBq of 177Lu activity/80 nmol of precursor, 6 GBq of 177Lu activity/120 nmol of precursor, 7.4 GBq of 177Lu activity/150 nmol of precursor, or 9.3 GBq of 177Lu activity/150 nmol of precursor (10 patients per group) every 2 mo. Safety was checked every 2 wk by laboratory tests, the prostate-specific antigen response was checked every 4 wk, and other effects were assessed by anamnesis. Results: The initial prostate-specific antigen response showed no correlation with treatment activity. However, 2 of 10, 4 of 10, 4 of 10, and 7 of 10 patients receiving doses of 4, 6, 7.4, and 9.3 GBq, respectively, were in partial remission 8 wk after completing all 3 cycles. This finding would be in line with but—because of low patient numbers—would not prove a positive dose-response relationship. Acute hematologic toxicity was also not correlated with treatment activity, and no more than 1 patient per group had grade 3/4 toxicity. Nevertheless, in contrast to the findings for the other groups, the mean platelet count in the 9.3-GBq group decreased chronically over time. Conclusion: If patients with diffuse red marrow infiltration and extensive chemotherapeutic pretreatments are excluded, then treatment activities of up to 3 injections of 9.3 GBq of 177Lu-PSMA-617 every 2 mo are tolerated well. Further dose escalation should be conducted with care, as the highest dose seems to be close to the maximum tolerable dose.